Pelaksanaan Pendidikan Sistem Ganda: Studi Kasus di Sekolah Menengah Industri Kerajinan Jepara - Amat Mukhadis (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
The Implementation of Dual System of Education: A Case Study at the Secondary School of Craft Industry Jepara. The study aims at exploring the characteristics of implementation of the dual system of education (PSG) at Secondary School of Craft Industry Jepara and at its counterpart institutions, and trying to find the constraints faced by the school and the counterpart institutions. The key persons of this qualitative case-study research were administrators and instructors of six small and medium scale industries. An in-depth interview, observation and documentation were used to collect data. Domain analysis was employed to analyze the data. Triangulation method was intended to obtain validity of the collected data. The findings indicate that the PSG was implemented as a field work ‘plus’, the majority of industry units involved were of small scale, the school council did not effectively mediate the school and the industry units, the PSG did not result in the expected added values yet, and there were many constraints faced by the school and the industry units in implementing the program.